1974
DOI: 10.1128/am.27.1.274-275.1974
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Acidaminococcus fermentans and Megasphaera elsdenii from Normal Human Feces

Abstract: Fecal bacterial cultures from 40 normal humans yielded Megasphaera elsdenii from four individuals and Acidaminococcus fermentans from 10 individuals, with two individuals having both organisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1974
1974
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…No other ASVs classified as M. elsdenii. The prevalence of M. elsdenii 4415 among the 30 microbiomes considered for this study (10%) was similar to previous reports on the occurrence of M. elsdenii in human stool (Sugihara et al, 1974). The abundance of M. elsdenii 4415 varied from 1.06% to 4.04% among the Me_D microbiomes (2.59 ± 0.86%; Figure 1A).…”
Section: Resultssupporting
confidence: 91%
“…No other ASVs classified as M. elsdenii. The prevalence of M. elsdenii 4415 among the 30 microbiomes considered for this study (10%) was similar to previous reports on the occurrence of M. elsdenii in human stool (Sugihara et al, 1974). The abundance of M. elsdenii 4415 varied from 1.06% to 4.04% among the Me_D microbiomes (2.59 ± 0.86%; Figure 1A).…”
Section: Resultssupporting
confidence: 91%
“…M. elsdenii is a Gram-negative, strictly anaerobic, coccus-shaped, nonmotile bacterium that inhabits the rumen of cattle and other ruminants [ 7 ] as well as the large intestine of humans [ 9 ] and pigs [ 10 ]. It is classified within the phylum Firmicutes (syn.…”
Section: Classification and Morphologymentioning
confidence: 99%
“…At the time of writing, only five species of the genus Megasphaera have been described (Rogosa 1971; Rainey 2009). The type species Megasphaera elsdenii (Marchandin et al , 2009) is a normal inhabitant of the rumen of cattle and sheep and is also found in the faeces and intestine of humans and pigs (Gutierrez et al , 1959; Sugihara et al , 1974; Hino et al , 1994; Hashizume et al , 2003; Gill et al , 2006; Marchandin et al , 2009; Faith et al , 2013), it also produces hydrogen (Ohnishi et al , 2010). Megasphaera cerevisiae , Megasphaera paucivorans , and Megasphaera sueciensis are brewery-associated species (Engelmann & Weiss, 1985; Juvonen & Suihko, 2006), while Megasphaera micronuciformis was recovered from a human liver abscess and a pus sample (Marchandin et al , 2003).…”
mentioning
confidence: 99%